A Putative Role for Cathepsin K in Degradation of AA and AL Amyloidosis - Röcken, Christoph (American Society for Investigative Pathology, 2001)
The aims of this study were to investigate the role of cathepsin K in the pathology of amyloidosis by demonstrating its presence in multinucleated giant cells (MGCs) adjacent to amyloid deposits, and determining its ability to degrade amyloid fibril proteins in vitro. The study was performed using autopsy and biopsy specimens from patients with AA or AL amyloidosis. In six (55%) patients with AA amyloidosis and seven (58%) patients with AL amyloidosis, variable numbers of CD68-immunoreactive MGCs were found adjacent to amyloid deposits. In each case strong cytoplasmic immunostaining for cathepsin K was found in MGCs; immunostaining of amyloid deposits was present in five (45%) patients with AA amyloidosis and three (25%) patients with AL amyloidosis. In vitro degradation experiments showed that recombinant cathepsin K completely degraded AA amyloid fibril proteins at pH 5.5 as shown by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Western blotting. Less effective degradation took place at pH 7.4 and there was no degradation in the presence of a general cysteine protease inhibitor (E64) or in the absence of cathepsin K. This is the first study to show that cathepsin K is expressed in MGCs adjacent to amyloid deposits and to demonstrate its ability to degrade amyloid fibril proteins.